The Influence of SARS-CoV-2 on the Polish Insolvency Law - Torbus, Andrzej (Teisė, 2023)
The impact of the covid-19 pandemic on the business environment created the risk of numerous insolvencies of entrepreneurs. The aim of this study is to discuss the impact of the COVID-19 pandemic on the Polish insolvency Law and to compare the solutions adopted in Poland with those in use in other countries.